Examining the Impact of Urban Sprawl on Agricultural Land and Local Economies in the Eastern Periphery of Delhi: A Geographical Perspective (International Journal of Food and Nutritional Sciences, 2023)
Land use and local economies are significantly impacted by urban sprawl, which is defined as the outward extension of city limits into adjacent rural areas in metropolitan areas. This study looks at how Delhi's eastern suburbs, which are rapidly becoming more urbanised, are impacted by sprawl and how it affects the local economy and agricultural land. A significant amount of the region's agricultural has historically been sustained by the eastern fringe, which included places like Ghaziabad, Noida, and portions of Faridabad. Nonetheless, there has been a noticeable change in this region's usage from agriculture to urban expansion in recent decades. Numerous reasons, such as growing land costs, government policies supporting urban growth, and the growing need for housing and infrastructure as Delhi's population grows, have contributed to this transition.